The role of frequency in the retrieval of nouns and verbs in aphasia. Issue 11 (1st November 2016) - Bastiaanse, Roelien; Wieling, Martijn; Wolthuis, Nienke
ABSTRACT: Background : Word retrieval in aphasia involves different levels of processing—lemma retrieval, grammatical encoding, lexeme retrieval, and phonological encoding—before articulation can be programmed and executed. Several grammatical, semantic, lexical, and phonological characteristics, such as word class, age of acquisition, imageability, and word frequency influence the degree of success in word retrieval. It is, however, not yet clear how these factors interact. The current study focuses on the retrieval of nouns and verbs in isolation and in sentence context and evaluates the impact of the mentioned factors on the performance of a group of 54 aphasic speakers. Aims : The main aim is to measure the effect of word frequency on the retrieval of nouns and verb by disentangling the influence of word class, age of acquisition, imageability, and lemma and lexeme frequencies on word retrieval in aphasia. Methods & Procedures : Four tests for retrieval of nouns, verbs in isolation, and infinitives and finite verbs were administered to 54 aphasic speakers. The influence of lemma and lexeme frequency, Age of Acquisition on the word retrieval abilities was analysed. Outcomes and Results : Word class, age of acquisition, and imageability play a significant role in the retrieval of nouns and verbs: nouns are easier than verbs; the earlier a word has been learned and the more concrete it is, the easier it is to retrieve. When performance is controlled for these factors, lemma frequency turns out to play a minor role: only in object naming does it affect word retrieval: the higher the lemma frequency of a noun, the easier it is to access. Such an effect does not exist for verbs, neither on an action-naming test, nor when verbs have to be retrieved in sentence context. Lexeme frequency was not found to be a better predictor than lemma frequency in predicting word retrieval in aphasia. Conclusions : Word retrieval in aphasia is influenced by grammatical, semantic, and lexical factors. Word frequency only plays a minor role: it affects the retrieval of nouns, but not of verbs.